Assembly of lightweight sandwich panels through joining by forming - Sampaio, R. F. V. (2021)
This paper is focused on the assembly of lightweight sandwich panels built upon the patented ‘Opencell’ structure concept. The objective is to investigate the possibility of joining the connection members of the core to the adjoining skin sheet by plastic deformation at ambient temperature, instead of welding or adhesive bonding. The methodology draws from earlier developments of the authors in joining by forming using the mortise-and-tenon concept to experimentation and finite element modelling of the assembly process in unit cells that are representative of the sandwich panels. It is shown that replacing welding by joining by forming allows fabricating sandwich panels from sheet materials that are difficult or impossible to weld while preventing thermal cycles that are responsible for causing metallurgical changes, distortions, and residual stresses. Replacing adhesive bonding by joining by forming circumvents the need of surface preparation, time for the adhesive to cure and environmental compliance, among other requirements